Frontiers in Organizing Processes Collaborating against Human Trafficking/Modern Slavery for Impact and Sustainability - Foot, Kirsten; Parks, Elizabeth Shun-Ching; Van der Watt, Marcel (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
As the crime of human trafficking/modern slavery is multifaceted, collaborating to counter it across sectors, disciplines, regions, and from local to international levels is widely understood to be of utmost importance. However, the processes of organizing and leading robust collaborations are complex and challenging, and to be sustainable, such processes must result in both positive outcomes for the collaborating partners and demonstrable progress toward countering human trafficking. Despite a growing body of published research on anti-trafficking collaboration, many aspects of it remain understudied. In this Special Issue of Societies, researchers and collaboration leaders in the anti-trafficking field share research findings and evidence-supported practices on how to conceptualize, catalyze, and support collaboration to generate and sustain constructive impacts.